Tourism research: A systematic review of knowledge and cross cultural evaluation of doctoral theses - Cristiana Oliveira; Adriaan De Man; Sergio Guerreiro (Tourism & Management Studies)
Tourism studies have become distinct in the past years due to the emergence of specialized journals, but also of universities, departments and research centers offering PhD programs, fundamental for the development of research and for the foundation of new scholars across the world. The purpose of this paper is to assess the recent development of knowledge by evaluating the nature of the dominant scientific fields and their core research subjects, through a cross cultural approach considering the UK, Spain, France, Germany, Italy and Portugal. This study addresses this gap and provides an original contribution through the analysis of the doctoral theses published between the years 2000-2013 in these countries. The selected research methodology is based on content analysis of keywords and concepts. Recommendations are offered for future developments.